Pendapatan, Risiko, dan Efisiensi Ekonomi Usahatani Bawang Merah di Kabupaten Bantul - Fauzan, Muhammad (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to evaluate the income of shallot farmers, to determine the risk of shallot production, and to examine the level of efficiency of shallot farmers in Bantul Regency. The primary data used in the study was obtained using structured questionnaire administered to 30 selected farmers. R/C ratio, coefficient of variation, and stochastic frontier production function were used to analyze the data. The result showed that shallot farming in Bantul Regency was profitable with incomes of Rp20,903,711/ha. The level of risks faced by farmers were quite high, it was 7.27%. The average level of technical, allocative and economical efficiency of shallot farmers were: 0.802; 0.889; and 0.929. This result shows that shallot farmers can increase their technical efficiency and allocative efficiency to achieve an economic efficient condition.